Evaluation of a voluntary control program for the detection of Bovine Leukemia Virus antibodies based on agar gel immunodiffusion test in dairy farms in Costa Rica - Dolz, Gaby (2015)
A total of 20 farms were analyzed repeatedly during five years using only the agar gel immunodiffusion test (AGIDT) as part of a voluntary control program of Bovine Leukemia Virus (BLV). After five years of cleaning up the herds for BLV based on AGIDT, blood samples from 332 dairy cows in these farms were collected and analyzed with the agar gel immunodiffusion test (AGIDT) and enzyme- linked immunosorbent assay (ELISA) to detect antibodies against BLV. The results of both assays were compared and evaluated. AGIDT detected 29.2% (97) and 16.0% (53) of the animals as positive and weak positive, respectively, whereas ELISA detected 58.2% (193) of the bovines as positive. The prevalence of BLV-antibodies determined with AGIDT in the dairy farms oscillated between 0% and 86%, ELISA determined prevalence between 28% and 100% in these farms. Although both techniques showed similar results in farms with high BLV-prevalence, ELISA detected a larger proportion of BLV-positives in one negative farm and in farms with low BLV-prevalence in AGIDT, leading to the assumption of an effective control in these farms. Our results strongly suggest that control of BLV based solely on AGIDT might complicate efforts of control programs, considering ELISA as the most adequate test for survey and control programs in Costa Rica.